The Ruggero Ceppellini Advanced School of Immunology and the Neapolitan Scientific Renaissance - Di Giacomo, Antonio (Frontiers in Immunology, 2019)
In this article the author, cofounder with Serafino Zappacosta and few other knowledgeable scientists of the Ruggero Ceppellini Advanced School of Immunology in 1991, discusses the significance of this initiative not only for the spreading of immunological culture among scientists—including those from disadvantaged Countries—but also for the resurgence of the city of Naples as a cultural pole of attraction for brilliant minds, as it was in its past history. This is a tribute to Serafino Zappacosta's foresightedness and generosity.